Improving the Ability to Write Procedural Texts Using the ARIAS Learning Model with Pop-Up Book Media - Ratih Tria Anggraini; Dessy Wardiah; Muhammad Ali (Journal of Social Work and Science Education, 2026)
This study aimed to enhance fifth-grade students’ procedural text writing skills at SD Negeri 11 Talang Kelapa by integrating the ARIAS learning model with Pop-Up Book media, addressing issues of low motivation and poor textual organization. Employing classroom action research across two cycles (each involving planning, action, observation, reflection), data were gathered via observation and written tests. Analysis utilized both quantitative and qualitative techniques. Significant improvement was observed. Mastery learning increased from 42.86% (pre-action) to 64.28% (Cycle I) and 89.29% (Cycle II). Students exhibited heightened motivation, engagement, and a better grasp of procedural text structure. The research innovatively combines the structured ARIAS motivational framework with interactive, three-dimensional Pop-Up Book media to teach procedural writing. This integrated approach provides teachers with an effective, replicable strategy for improving writing instruction and student engagement in elementary classrooms. The study confirms the efficacy of the ARIAS-Pop-Up Book synergy, offering a validated model for enhancing both the cognitive and affective dimensions of procedural writing skills.